Inclusive deliberation and action in emerging RRI practices: the case of neuroimaging in security management. Issue 1 (2nd January 2016) - de Jong, Irja Marije; Kupper, Frank; Broerse, Jacqueline
ABSTRACT: What does it mean to facilitate inclusive deliberation, a core aspect of Responsible Research and Innovation, at a very early stage in a controversial field such as security? We brought neuroscientists and security professionals together in a step-by-step fashion – interviews, focus groups and dialogue – to construct imaginaries of neuroimaging applications. Neuroscientists and security professionals related differently to neuroimaging investigation. Some of what the security professionals seek in neuroscience might better be provided by social psychology. However, neuroimaging can be imagined to aid professionalization through a theory-informed security management practice. Post-hoc reflection interviews were performed to identify impacts, such as reflexivity of the stakeholders, the formation of new relationships and actions. Our use of social psychology as a low-technology alternative brought into sharper focus where potential responsible security sector uses of neuroimaging lie. However, without on-going facilitation of interactions, this imaginary is likely to dissolve.